A study relationship between types of parenting styles academic motivation among adolescencents in Johor Bahru - Nur Ain Syuhada, Binti Shukor (Universiti Malaysia Sarawak (UNIMAS), 2017)
The issue of parenting styles has been highlighted as a major component of academic motivation among adolescents who make up the secondary school population. This is because, there is a belief that each parenting style sets its own demands with respect to the conduct of learners and standards that they have to meet. Moreover, parents playa highly influential role in their children's development. It is generally agreed that parenting style influences self-efficacy, self-esteem, and identity development, which are associated with academic achievement of students. In addition, the progress in children's achievement is influenced by the decision that is made by both parents and their children to cooperate or confront each other. The aim of this review is to analyze the different aspects of parenting styles which affect the academic motivation of adolescents. This study provides a comprehensive interpretation of different studies about how parenting styles affect academic motivation among adolescents in Johor Bahru. Also, as there are many issues on their academic performance faced by ado lescents, so there should be a right parenting skill that should be developed by the parents which can help them in overcoming those issues.